2016
DOI: 10.1099/jgv.0.000430
|View full text |Cite
|
Sign up to set email alerts
|

A newly discovered flavivirus in the yellow fever virus group displays restricted replication in vertebrates

Abstract: A novel flavivirus, provisionally named Bamaga virus (BgV), was isolated from Culex annulirostris mosquitoes collected from northern Australia. Phylogenetic analysis of the complete nucleotide sequence of the BgV genome revealed it clustered with the yellow fever virus (YFV) group, and was most closely related to Edge Hill virus (EHV), another Australian flavivirus, with 61.9 % nucleotide and 63.7 % amino acid sequence identity. Antigenic analysis of the envelope and pre-membrane proteins of BgV further reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 43 publications
2
42
1
Order By: Relevance
“…The pr-M furin cleavage site for KRBV, McPV, and HaCV occurs between amino acids 172 and 173 and follows the consensus established for other flaviviruses (23), suggesting that the cleavage is efficient, unlike for some cISFs (e.g., PaRV) that exhibit inefficient pr-M cleavage (15). …”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…The pr-M furin cleavage site for KRBV, McPV, and HaCV occurs between amino acids 172 and 173 and follows the consensus established for other flaviviruses (23), suggesting that the cleavage is efficient, unlike for some cISFs (e.g., PaRV) that exhibit inefficient pr-M cleavage (15). …”
Section: Resultsmentioning
confidence: 62%
“…Assignments for dISFs varied between insect only and vector borne, with those phylogenetically related to Lammi virus (LAMV) being assigned to the insect-only group, and those related to Barkedji virus (BJV) assigned to the vector-borne group. Bamaga virus (BgV), another recently discovered Australian flavivirus with limited replication in vertebrates, grouped closely with VIFs, consistent with its phylogenetic position (23). It was noteworthy that the flaviviruses with no known vector generally grouped closely with vector-borne viruses, with the exception of the highly divergent Tamana bat virus sequence, which was predicted to be associated only with a vertebrate host in this analysis.…”
Section: Resultsmentioning
confidence: 78%
“…We have previously shown that BgV replication could be detected in OK, HEK293 and BHK cells but not in Vero, DF-1, or RK-13 cells [11]. BgV replication was assessed in a wider range of insect and vertebrate cell lines at 28˚C or 37˚C, including in cell lines used in our previous study, as shown in Table 1.…”
Section: Bgv Is Host-restricted In Some Vertebrate Cells In Vitromentioning
confidence: 99%
“…As part of our ongoing efforts to characterise flavivirus host-restriction, this study aimed to investigate Bamaga virus attenuation and the mechanisms involved. Bamaga virus (BgV) was recently isolated from archival mosquito samples of the Culex sitiens subgroup collected in 2001 and 2004 from Cape York, Far North Queensland, Australia [11] and found to be phylogenetically most closely related to Edge Hill virus and other members of the yellow fever group. Despite this close genetic relationship, initial in vitro characterisation showed that BgV displayed a restricted host range, as it was only able to replicate efficiently in a subset of vertebrate cell lines, and displayed a host-restricted phenotype in CD1 mice [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation